A Systematic Literature Review of Integrated Learning Models for Skills Development in Industry-Academia Partnerships: Preparing Workforce for Industry 4.0 - Ricky Cahyasari Putra; Mokhamad Syaom Barliana; Mumu Komaro; Aam Hamdani (VANOS Journal of Mechanical Engineering Education, 2025)
The Industry 4.0 revolution has created significant skills gaps between formal education outcomes and evolving industry requirements, necessitating innovative industry-academia partnerships. This systematic literature review analyzes integrated learning models addressing these challenges. Following PRISMA guidelines, we searched Scopus, Web of Science, ERIC, and Science Direct databases (2021-2025) using keywords combinations of "industry-academia partnerships," "integrated learning models," and "vocational education." From 119 initial articles, 42 met inclusion criteria after duplicate removal and quality assessment using MMAT. Thirteen distinct learning models were identified: Competency-Based Training, Work-Integrated Learning, Work-Based Learning, Teaching Factory, Teaching Industry, Production-Based Education and Training, Cooperative Education, Vocational Pedagogy, Simulated Work Environment, Industrial Incubator, Apprenticeship Plus, School-Industry Partnership, and Technopark. Results demonstrate that strategic integration of multiple models creates more comprehensive educational ecosystems than individual implementations. A holistic framework categorizing models into five groups provides practical guidance for contextual adaptation based on institutional capacity and industry needs.